Morphology and identification of first instars of the European and Mediterranean blowflies of forensic importance. Part II. Luciliinae. Issue 4 (3rd December 2012) - SZPILA, K.; HALL, M. J. R.; PAPE, T.; GRZYWACZ, A.
Abstract : First instars of Lucilia ampullacea Villeneuve, Lucilia caesar Linnaeus, Lucilia cuprina Weidemann, Lucilia richardsi Collin, Lucilia sericata Meigen and Lucilia silvarum Meigen (Diptera: Calliphoridae) are thoroughly documented with scanning electron microscopy images, light microscopy photographs and line drawings. The following morphological structures are documented: pseudocephalon, antennal complex, maxillary palpus, facial mask, cephaloskeleton, thoracic and abdominal spinulation, spiracular field, and posterior spiracles. New diagnostic features of the cephaloskeleton are presented and the spinulation of the abdominal segments is described. Earlier descriptions are summarized and major discrepancies with the current study are discussed. The present results allow for the clarification, correction and, especially, complementing existing information provided by numerous authors. The first instar larva of L. richardsi is described for the first time and an identification key to the first instars of European species of Lucilia Robineau‐Desvoidy of forensic importance is presented.